Social portrait of Europe. (Theme 3: Population and social conditions. Monographs, 1998)
This third edition of the Social Portrait provides a review of the current social trends in the 15 Member States of the EU. The data used come mainly from the national statistical institutes and are based largely on harmomised sources available in Eurostat, such as the European Labour Force Survey (LFS) and the European Community Household Panel (ECHP). The ten chapters each focus ona different area of social policy: (i) economic background, (ii) population, (iii) households and families, (iv) education and training, (v) labour market, (vi) working environment, (vii) earnings, (viii) income, (ix) consumption and housing conditions, (x) life expectancy and health.